Fiestas Patrias Mexican Independence 2000 - Parade - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the 2000 Fiestas Patrias Parade celebrating Mexico's Day of Independence, hosted by the San Jose American GI Forum.